Kesadaran dan Perjuangan Buruh Jawa Timur Dalam Menolak Upah Murah Di Era Pandemi - Rosselina Mulya Rahma; Agus Macfud Fauzi; Silkania Swarizona (Jurnal Community, 2022)
At the end of 2021, the East Java labor alliance flocked to carry out demonstrations at several important points, such as the Grahadi Building in Surabaya and district or city offices from each region. This demonstration was attended by workers from various regencies or cities in East Java, such as Gresik, Surabaya, Malang, Kediri, and so on. This action was carried out with the aim of demanding an increase in labor wages by 2022. Unlike the previous year, the demonstration was carried out in the midst of the Covid-19 pandemic in Indonesia. Departing from this reality, the author was prompted to analyze the existence of awareness and struggle of East Java workers in demanding wages during the Covid-19 pandemic which was analyzed using Karl Marx's theory of Awareness and Class Struggle. This research utilizes a qualitative approach with a literature study method. The source of this research comes from secondary data, namely online news, books, and journals. The results of this study show that even in the Covid-19 pandemic situation in Indonesia and in the pouring rain, all East Java labor alliances still take action to take to the streets in rejecting cheap wage increases in 2022, as predicted by Karl Marx.